Preparation of scaffold systems for cell cultivation using cryogenic grinding of thin layers of polymeric fibers - Křížková, Barbora (Univerzita Pardubice, 2012)
The work was focused on cryogenic grinding of electrospun poly-epsolin-caprolactone nano/micro-mesh submerged in liquid media to prepare a microsystem applicable as a scaffold for cell growth. Optimization of the grinding process involved examination of various parameters influencing the quality of the ground product. Characterisation and biocompatibility evaluation provided evidence of the applicability of the system in cell scaffolding.
Příprava nosičových systémů pro růst buněk pomocí kryogenního mletí tenkých vrstev polymerních vláken
Keywords: Kryogenní mletí; poly-epsilon-kaprolakton; tenké vrstvy polymerních vláken; mikrosystém; charakterizace; Cryogenic grinding; poly-epsilon-caprolactone; nano/micro-mesh; microsystem; characterization